Bimbingan Kelompok Teknik Modeling Untuk Mengoptimalkan Perencanaan Karier Siswa Sekolah Menengah Pertama: Kajian Naratif - Sedyawati, Sedyawati; Muslihati, Muslihati (Universitas PGRI Kanjuruhan Malang, 2025)
This article narratively explores the use of the modeling technique in group counseling as an effort to optimize the career planning of junior high school students which is a critical period to determine career planning. The study employs a Narrative Review method. From the data collection process were analyzed in accordance with the research objectives. The modeling technique allows students to learn by observing the behaviors, values, and skills demonstrated by a model. References in this article are derived from various journals that discuss the effectiveness of group counseling and modeling techniques in supporting students' career development. The purpose of this study is to explore the effectiveness of the modeling technique in group counseling for enhancing junior high school students’ career planning. The review results indicate that this technique is effective in improving students' understanding of career options, strengthening their motivation, and building their confidence in designing their future. Additionally, the modeling technique helps uncover students' interests and abilities. In conclusion, the modeling technique in group counseling has proven to be an effective approach to supporting junior high school students' career planning. Its implementation in schools is recommended to help students prepare for their future in a more directed and confident manner.